THE ASSOCIATION BETWEEN MENTAL TOUGHNESS, COMPETITIVE ANXIETY, GOAL ORIENTATION, AND PERFORMANCE IN SCHOOL ATHLETES: A SYSTEMATIC LITERATURE REVIEW - Shapri, Jessyla @ Assad; Wazir, Mohd Rozilee Wazir Norjali; Nazarudin, Mohamad Nizam (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
This systematic literature review synthesizes current evidence on the interrelationships between mental toughness, competitive anxiety, goal orientation, and athletic performance among school athletes. Despite extensive research on these constructs individually, their integrated effects within youth sport contexts remain insufficiently understood. Guided by the PRISMA framework, a comprehensive search was conducted across five major databases (PubMed, Scopus, ScienceDirect, SpringerLink, and Web of Science), supplemented by Google Scholar. Studies published between 2016 and 2023 were screened against predefined inclusion criteria, yielding a final sample of 65 empirical studies. The findings reveal that mental toughness consistently functions as a key moderating and mediating variable, attenuating the negative impact of competitive anxiety on performance outcomes. Task-oriented goal orientation shows a more adaptive association with performance stability and psychological resilience than ego-oriented frameworks, particularly under high-pressure conditions. Conversely, competitive anxiety, especially its cognitive dimension, tends to impair performance, although its effects vary depending on individual psychological profiles and contextual factors such as coaching style and motivational climate. Furthermore, psychological skills training interventions, including goal setting, imagery, and mindfulness-based approaches, show positive but context-dependent effects on enhancing mental toughness and regulating anxiety. Overall, the review highlights the multidimensional and interactive nature of psychological determinants in youth sport performance, supporting the need for integrated theoretical models and individualized intervention strategies. Methodological inconsistencies and the predominance of cross-sectional designs remain key limitations within the literature. Future research should prioritize longitudinal and cross-cultural investigations to better capture developmental trajectories and contextual variability. The findings provide practical implications for coaches, educators, and sport psychologists in designing holistic, evidence-based athlete development programs that balance performance optimization with psychological well-being.